Visitors from beyond the Grave: Ghosts in World Literature - Israel Muñoz-Gallarte (Classica Digitalia: Humanitas Supplementum - Estudos Monográficos, 2019)
The monograph deal with the topic of ghosts in universal literature from a polyhedral perspective, making use of different perspectives, all of which highlight the resilience of these figures from the very beginning of literature up to the present day. Therefore, the aim of this volume is to focus on how ghosts have been translated and transformed over the years within literature written in the following languages: Classical Greek and Latin, Spanish, Italian, and English.